Model Pengelolaan Keuangan Berbasis Literasi Dan Iklusi Keuangan : Study Pada Masyarakat Petani Desa Pombewe - Ferdiansyah Ferdiansyah; Darman Darman; Anisah Anisah; Munawara Munawara (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This research aims to produce a Financial Management Model Based on Financial Literacy and Financial Inclusion: A study of farming communities in Huntap Pombewe. Meanwhile, the research time until the completion stage is estimated to be approximately 6 months starting from October 2023 to March 2024. This research is basic research. The population and samples in this study were taken from 30 farmers in Huntap Pombewe through collaboration using a cluster sampling approach in 2 Huntap Pombewe sub-districts, as well as random sampling based on the criteria of type, duration and average level. business profits. Primary data collection was carried out using a survey method using a questionnaire. The data analysis technique used is descriptive statistical analysis and SEM-PLS with the help of Smart PLS software. The research results show that based on the results of data processing from the structural model, the results obtained show that the Financial Literacy variable has a significant positive effect on Financial Inclusion: A Study of the Farming Community in Huntap. Financial Literacy has a significant positive effect on Financial Management: Study of the Farming Community in Huntap Pombewe. Financial Inclusion has a significant positive influence on Financial Management, and Financial Inclusion can mediate positively Financial Literacy on Financial Management: Study of the Farming Community in Huntap Pombewe.